Effectiveness of Intradialytic Stretching Exercises In Preventing Muscle Cramps in Individuals Undergoing Hemodialysis : A Systematic Review - Tadi Tadi; Ika Yuni Widyawati; Ira Suarilah (Jurnal Ners, 2026)
Introduction: Individuals with Chronic Kidney Disease (CKD) may experience symptoms of uremic syndrome. Intradialytic stretching exercises have been proposed as a method to increase activity levels while reducing uremic symptoms. Muscle cramps are a common complication of hemodialysis treatment and often lead to early termination of sessions, therefore, timely intervention to address muscle cramps in hemodialysis patients is a critical priority. Objective: To systematically analyse the effectiveness of intradialytic stretching exercises on muscle cramps among individuals undergoing hemodialysis Methods: A systematic review was conducted through five major databases: Scopus, PubMed, Science Direct, ProQuest, and Wiley, for the last five years publication (2020 to 2025). Eligible studies included those that implemented intradialytic stretching exercises interventions focused on muscle cramps for individuals undergoing hemodialysis. Data extracted included study characteristics, sample demographics, design, and measured outcomes. Study quality was assessed using the Joanna Briggs Institute (JBI) critical appraisal tool, and findings were synthesized through narrative analysis. Result: Eleven studies (n=11) that obtained JBI quality assessment scores ranging from 77% to 92% were included in the final analysis, involving 809 participants from 7 countries, with intervention durations ranging from 4 to 24 weeks. The reviewed intradialytic stretching exercise interventions addressed aspects of muscle cramps, urea levels, and fatigue. Conclusion: Intradialytic stretching exercises demonstrate significant potential in preventing muscle cramps of individuals undergoing hemodialysis. Further research is needed to evaluate long-term outcomes and optimise intervention designs.